THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN USERS OF J&T EXPRESS SERVICE IN THE SURAKARTA - Sejati, Septy Agil (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study aims to analyze the effect of service quality (X) and customer satisfaction (Z) on customer loyalty (Y) for J&T Express service users in the Surakarta Residency. The population in this study were J&T Express service users in the Surakarta Residency and obtained a sample of 90 respondents using the Purposive Sampling technique. The data collection method uses a questionnaire and is processed using Partial Least Square (PLS) analysis with SmartPLS 3.0 software. The results of this study indicate that service quality has a significant positive effect on customer satisfaction, customer satisfaction has a significant positive effect on customer loyalty, service quality has a significant positive effect on customer loyalty, and service quality has a significant positive effect on customer loyalty mediated by customer satisfaction.